POLITICAL ELITES OF KYRGYZSTAN: OW THEY APPEARED AND HOW THEY INTERACT - NOGOYBAEVA, Elmira (CENTRAL ASIA AND THE CAUCASUS, 2007)
Since 1991, that is, from the very first days of Kyrgyzstan’s independence, its elites have been following their own paths and developing in ways that do not fit into other models or nation–building projects. This was, in fact, a new stage in the elite-forming process. Before this time, the local elites developed within larger states and followed the prevailing patterns: partially within the Kokand Khanate, then later within the Russian Empire and the Soviet state. The Kyrgyz elites as a system-forming factor of the Kyrgyz nation mainly adapted themselves to the conditions offered. There are two sides to the fairly frequent phenomenon whereby one nation develops within another. On the one hand, a nation threatened with assimilation, dispersal, or extermination can save itself by moving into the gravitational field of a stronger entity. This brings security and the chance of self-preservation and, sometimes, modernization. It acquires an elite of its own formed within the new state and may either change itself within the same state to become a system-forming nation or descend to the lower levels of social development. On the other hand, the nation loses the opportunity to develop its own symbols, traditions, and institutions; it is forced to adapt itself to the dominant subject or, to be more exact, to imitate it. For nearly a century the political culture of Kyrgyzstan developed as a Soviet political culture characterized by the monopoly of one party and the rigid hierarchy of elites replenished through a closed recruitment system. Today, in the context of state-building, prime importance is attached to the formation of inde-pendent and transitional elites across the post-Soviet expanse that are searching for a political system best suited to Kyrgyz national specifics with all the appropriate forms of political organization and institutions. Since the country did not have any local recruiting traditions or principles of functioning as it moved away from the communist toward democratic development paradigms, new forms of recruitment and organization of the new/old elites in Kyrgyzstan appeared. Since 1991, the political elites of Kyrgyzstan (which did not differ much from hardly any of the other post-Soviet countries) have been developing and functioning as the elites of an independent state engaged in nation-building and institutionalization within their geographic and political areas.